DINAMIKA POLITIK PARTAI LOKAL DI ACEH MENJELANG PEMILU 2024: ANALISIS UNDANG-UNDANG PEMILU DAN PARTAI LOKAL - Sari, Elidar; Rahman, Arif; Faisal, Faisal; Muksalmina, Muksalmina (Program Studi Magister Hukum Universitas Malikussaleh, 2024)
Abstract Local parties in Aceh represent a unique and significant political phenomenon in the context of Indonesian democracy. These local parties play a strategic role in representing the aspirations of the Acehnese people, who have special autonomy and a history of conflict with the central government. However, local parties in Aceh also face challenges and complex political dynamics leading up to the 2024 elections. This article aims to analyze the political dynamics of local parties in Aceh using the framework of election laws, local parties, and criminal sanctions. The research method employed in this article is qualitative research, utilizing data collection techniques such as literature studies, interviews, and observations. The research findings indicate that the current election laws provide space for local parties in Aceh to participate in elections, but also impose strict requirements and limitations. Local parties in Aceh have also undergone changes in terms of ideology, mass base, coalitions, and electoral strategies. Additionally, local parties in Aceh also have the potential to be involved in practices of electoral bribery and violations that could result in criminal sanctions. This article recommends that local parties in Aceh enhance their internal quality, accountability, and political representation, while also maintaining the integrity of elections and the law. Keywords: 2024 elections; local parties; Aceh; electoral violations; legal awareness